Impulse radio multipath characteristics and diversity reception - Cramer, R.J.-M.; Win, M.Z.; Scholtz, R.A. (1998 IEEE International Conference on Communications, 1998)
Delay-and-sum beamforming is applied to both ideal and measured ultra-wideband (UWB) signals. The results of propagation measurements are also used directly to estimate the performance of an UWB communication system and to characterize design tradeoffs.